Implementation Of Artificial Neural Networks (ANN) For Prediction Of Students High School Graduations - Roza, Pora; Junjung, Mardan (Jurnal Sains dan Informatika, 2016)
This study applies neural network to predict students graduation rates. The purpose of this study is to see the results of prediction, so that users can make changes to existing systems at their respective schools, to improve student graduation rate for the years to come based on the graduation of the past that have been predicted. Data was collected through observations and interviews conducted at the place to do research, either by the teachers and students concerned. The data obtained are collected and processed, analyzed and studied. Formulated so that later can do further research. Research using neural network techniques, using Matlab software. The results showed that neural networks can process the data change at any time or for years.